RANCANG BANGUN SISTEM SMART HOME BERBASIS IOT MENGGUNAKAN NODEMCU V3 (ESP8266) DAN BLYNK UNTUK MENINGKATKAN KEAMANAN DAN EFISIENSI PADA RUMAH TANGGA - Noval Valentino Natanael Karouw; Calvin Evangelista Johanes Mamahit; Janne Deivy Ticoh (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
The development of Internet of Things (IoT) technology has encouraged the integration of electronic devices in home automation systems known as smart homes. This system allows for automatic and remote monitoring, control, and security of homes via the internet. This study aims to design and build a home system to improve security and energy efficiency in households. The developed system integrates various sensors and actuators, including MQ-2 gas sensors, fire sensors, magnetic door sensors, ultrasonic sensors, relays, servo motors, buzzers, and an ESP32-CAM module as a monitoring camera. NodeMCU V3 (ESP8266) functions as a system controller that is connected to the internet network via WIFI and communicates with the Bynk application to send data, notifications, and control devices in real-time. In addition, this system is equipped with solar panels and batteries as backup power sources so that this system continues to function properly during power outages. The results of this study indicate that the designed smart home system is able to work integratedly and stably in detecting potential hazards, thereby increasing energy efficiency and comfort. NodeMCUv3 (ESP8266) and Blynk can be an effective, efficient, and affordable solution for improving household security and efficiency. This research is expected to serve as a reference in the development of IoT-based smart home systems in residential environments.